1978
DOI: 10.1111/j.1476-5381.1978.tb08632.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Origin of Plasma Catecholamines After Decapitation: A Study in Normal and Diabetic Rats

Abstract: The concentrations of catecholamines and the activities of dopamines‐hydroxylase were measured in blood obtained from decapitated diabetic and aged‐matched control rats. The activity of dopamines‐hydroxylase in blood from diabetic rats was much greater (5 fold) than that seen for control rats. For both diabetic and control rats, decapitation was accompanied by an increase in levels of adrenaline and noradrenaline with no change in the activity of plasma dopamines‐hydroxylase. The results are consistent with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 7 publications
0
3
1
Order By: Relevance
“…The isolation procedure involves exhaus tive washing of the vascular tissue and it can be assumed that the CAs in the final tissue prepa ration are firmly bound. It has been shown that EP is the predominant CA present in blood obtained from decapitated rats (Berkowitz and Head, 1978) and in the present study EP reflected only a small percentage (4.4% for the rat microvessels) of the total CA content of microvessel preparations. Furthermore the max imal concentration of NE in blood from decapi tated rats was reported to be less than 0.01 tig m l"1 plasma (Berkowitz and Head, 1978), the NE contents of microvessel preparations (i.e.…”
Section: Discussionmentioning
confidence: 55%
“…The isolation procedure involves exhaus tive washing of the vascular tissue and it can be assumed that the CAs in the final tissue prepa ration are firmly bound. It has been shown that EP is the predominant CA present in blood obtained from decapitated rats (Berkowitz and Head, 1978) and in the present study EP reflected only a small percentage (4.4% for the rat microvessels) of the total CA content of microvessel preparations. Furthermore the max imal concentration of NE in blood from decapi tated rats was reported to be less than 0.01 tig m l"1 plasma (Berkowitz and Head, 1978), the NE contents of microvessel preparations (i.e.…”
Section: Discussionmentioning
confidence: 55%
“…Evidence for a DAmediated dilation of the dog renal vascular bed and dog hindlimb vascular bed has been presented [Goldberg et al, 1978;Bell et al, 1975] and the actions of DA thought to involve postjunctional receptors. Our find ings of small levels of DA in the vasculature and our previous finding indicating minimal circulating levels of DA in the rat [Berkowitz and Head, 1978] would argue against a prom inent role for endogenous DA in modulating cardiovascular responses. It is possible, how ever, that vascular DA may play a role in car diovascular regulation under conditions where the natural transmitter substance (NE) is depleted.…”
Section: Discussioncontrasting
confidence: 35%
“…Decapitation is associated with an increase in the circulating catecholamines due to a stimulation of secretion by the adrenal medulla (Berkowitz and Head, 1978). Thus, catecholamine quantification in serum might mimic, at least in part, a situation of stress exposure rather than basal levels of catecholamines.…”
Section: Npymentioning
confidence: 98%